William Tyndale1. (February 2015) - Werrell, Ralph S.
This article considers four important aspects we need to understand William Tyndale: the Person; the Father of Modern English; the Translator; and the Theologian. Discussed in the first section is what Tyndale reveals about himself as a person, especially using autobiographical illustrations from his childhood. When Tyndale went to Europe, we have to introduce some speculation regarding his movements, but these are kept to a minimum. Tyndale the Father of Modern English shows the influence Tyndale had in changing Middle English into Modern English when the change was taking place. Tyndale the Translator reveals his genius as a translator, but also the help he got from his boyhood reading of Trevisa's Dialogue between a Knight and a Clerk on the importance of an English Bible, and Trevisa's teaching about translation, in the introduction to his translation of Higden's Polychronicon. Tyndale's Bible translation still has a relevance for translators today. Tyndale the Theologian points to Tyndale's genius as a theologian. It starts by stressing that he disagreed with Luther, even in his earliest works, which are often said to reveal his Lutheranism. It argues that although there were some important differences between them, Calvin's theology was closer to Tyndale's. Tyndale stressed the importance of God the Father and the Christian as a child of God. Tyndale's theology started with the Fall, and man's spiritual death; before going on to God's promises of salvation through the blood of the sacrifices that point to the final sacrifice of Christ on the cross.